N6-Methyladenosine Induced miR-34a-5p Promotes TNF-α-Induced Nucleus Pulposus Cell Senescence by Targeting SIRT1 - Zhu, Hao; Sun, Bao; Zhu, Liang; Zou, Guoyou; Shen, Qiang (Frontiers in Cell and Developmental Biology, 2021)
Low back pain is tightly associated with intervertebral disc degeneration (IVDD) and aberrant nucleus pulposus (NP) is a critical cause. miRNAs N6-methyladenosine (m6A) modification accounts for the TNF-α-induced senescence of NP cells. Methyltransferase like 14 (METTL14) was identified in the NP cells of IVDD patients. METTL14 was knocked down or overexpressed in HNPCs to observe the effects on cell viability, cell cycle arrest, and cell senescence. miR-34a-5p was screened as the METTL14-associating miRNA. The miR-34a-5p inhibitor was employed to examine the effects on cell viability, cell cycle arrest, and senescence. Silent mating type information regulator 2 homolog-1 1 (SIRT1) was overexpressed to investigate its effects on cell senescence in the presence of the inhibitor and the mimic of miR-34a-5p. METTL14 expression positively correlated with m6A and TNF-α expression in HNPCs. The knockdown of METTL14 led to the inhibition of the TNF-α-induced cell senescence. METTL14 overexpression promoted cell senescence. METTL14 regulated the m6A modification of miR-34a-5p and interacted with DGCR8 to process miR-34a-5p. The miR-34a-5p inhibitor inhibited the cell cycle senescence of HNPCs. miR-34a-5p was predicted to interact with the SIRT1 mRNA. SIRT1 overexpression counteracted the miR-34a-5p-promoted cell senescence. METTL14 participates in the TNF-α-induced m6A modification of miR-34a-5p to promote cell senescence in HNPCs and NP cells of IVDD patients. Downregulation of either METTL14 expression or miR-34a-5p leads to the inhibition of cell cycle arrest and senescence. SIRT1 mRNA is an effective binding target of miR-34a-5p, and SIRT1 overexpression mitigates the cell cycle arrest and senescence caused by miR-34a-5p.